Pengaruh Ekspor Dan Impor Kopi Terhadap Neraca Perdagangan Di Indonesia Dalam Perspektif Ekonomi Islam Tahun 2014-2023 - Putri, Regita Ayu; Etika, Citra; Hasyimi, Diah Mukminatul (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This study aims to analyze the effect of coffee exports and imports on Indonesia's trade balance from2014 to 2023 within the perspective of Islamic economics. The research uses a quantitative approachwith a multiple linear regression model based on annual time series data. The results show that bothcoffee exports and imports have a significant influence on the trade balance, both partially andsimultaneously, but with a negative impact. From the Islamic economic perspective, trade should beconducted fairly, balanced, and must bring benefit (maslahah) to society. These findings reflect a lackof balance in coffee export and import activities that must be addressed to align with Shariaprinciples. The novelty of this study lies in combining quantitative analysis with Islamic economicperspectives, which has rarely been applied in previous research on coffee trade. This researchrecommends strengthening export value, improving logistics efficiency, and controlling unproductiveimports. The findings are expected to provide insights for policymakers and future researchers inbuilding a sustainable and just coffee trade system.